2010
DOI: 10.1038/nmat2766
|View full text |Cite
|
Sign up to set email alerts
|

Filled and glycosylated carbon nanotubes for in vivo radioemitter localization and imaging

Abstract: Functionalization of nanomaterials for precise biomedical function is an emerging trend in nanotechnology. Carbon nanotubes are attractive as multifunctional carrier systems because payload can be encapsulated in internal space whilst outer surfaces can be chemically modified. Yet, despite potential as drug delivery systems and radiotracers, such filled-and-functionalized carbon nanotubes have not been previously investigated in vivo. Here we report covalent functionalization of radionuclide-filled single-wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
208
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(210 citation statements)
references
References 41 publications
2
208
0
Order By: Relevance
“…[ 38 ] Previous studies have also shown that well-dispersed CNTs are excreted via a biliary pathway after hepatocyte uptake. [ 39,40 ] Hepatocytes in the liver can clear foreign particles via an endocytosis mechanism. [ 41,42 ] Our TEM ,C)).…”
Section: Mwcnts Enter Hepatocytesmentioning
confidence: 99%
“…[ 38 ] Previous studies have also shown that well-dispersed CNTs are excreted via a biliary pathway after hepatocyte uptake. [ 39,40 ] Hepatocytes in the liver can clear foreign particles via an endocytosis mechanism. [ 41,42 ] Our TEM ,C)).…”
Section: Mwcnts Enter Hepatocytesmentioning
confidence: 99%
“…The covalent functionalization of the radionuclidefilled SWNTs were used as radio probes [210] . The intravenous (IV) administration of these 125 I-loaded SWNTs was tracked in vivo using SPECT.…”
Section: Coupling With Other Contrast Agentsmentioning
confidence: 99%
“…A major advantage of nanoparticles for theranostics would be the high payload of both therapeutic agent and imaging probe that can be delivered to the target tissue. Specific examples of theranostic agents currently under investigation include liposomal vesicle formulations containing cytostatic drugs and MR contrast agents [28,29], carbon nanotubes as multifunctional carriers for radioisotopes for treatment and imaging [30], and dendriworms for efficient delivery of siRNA (small interfering RNA) visualised by optical imaging or MRI [31]. An additional new approach in theranostic strategies is 'cellular theranostics'.…”
Section: Theranosticsmentioning
confidence: 99%